2011
DOI: 10.1089/dia.2011.0025
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Sitagliptin on 24-H Glycemic Changes in Japanese Patients with Type 2 Diabetes Assessed Using Continuous Glucose Monitoring

Abstract: Sitagliptin decreased the average glycemic level and also improved 24-h glycemic fluctuation, including postprandial hyperglycemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
21
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 19 publications
3
21
0
Order By: Relevance
“…First, the number of subjects enrolled was relatively small. The number of subjects studied in some clinical previous investigations (Mori et al, 7 Osonoi et al, 26 and Kim et al 27 ) of glucose fluctuations affected by antidiabetes drugs using CGM was similar to that of our study. Therefore, 26 patients might be enough to verify the effects of teneligliptin on glucose fluctuation using CGM such as in our pilot study.…”
supporting
confidence: 88%
See 2 more Smart Citations
“…First, the number of subjects enrolled was relatively small. The number of subjects studied in some clinical previous investigations (Mori et al, 7 Osonoi et al, 26 and Kim et al 27 ) of glucose fluctuations affected by antidiabetes drugs using CGM was similar to that of our study. Therefore, 26 patients might be enough to verify the effects of teneligliptin on glucose fluctuation using CGM such as in our pilot study.…”
supporting
confidence: 88%
“…5,6 Therefore, DPP-4 inhibitors, incretin-based agents, are a promising new class of antidiabetes drug that can improve glucose fluctuations in patients with type 2 diabetes. 7 Teneligliptin, a novel DPP-4 inhibitor, is substantially metabolized in the liver, and its concentration in the serum is not affected even by severe renal impairment. 8 This suggests that teneligliptin can be administered to patients with renal impairment due to diabetic nephropathy without the need for dose adjustments.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, we considered that MAGE was likely to make a more significant difference than SD. In this regard, postprandial hyperglycemia is considered to be due to the synergetic effects of gradual glucose absorption of α-GI and improvement of early-stage insulin secretion by glinide [21]. As it has been reported that MIT/VOG improves glycemic control in terms of medication adherence [22], the use of MIT/VOG, which is considered to act as both α-GI and glinide, is considered significant.…”
Section: Discussionmentioning
confidence: 99%
“…In 2009, the dipeptidyl peptidase-4 (DPP-4) inhibitor sitagliptin was approved as the first incretin enhancer for use in Japan [4][5][6][7][8][9][10][11] . Although it has been suggested that seasonal fluctuations of hemoglobin A1c (HbA1c) are noted in patients with type 2 diabetes, no reports have been published concerning the efficacy of antidiabetic agents for such fluctuations.…”
Section: Introductionmentioning
confidence: 99%